Periodontal Surgery In Gingival Recession With Subepithelial Connective Tissue Graft Technic - Erianti Dewi Utami (Denta Journal Kedokteran Gigi, 2017)
Background: Periodontal tissue is a connective tissue that sorrounding the tooth and consists of gingiva, cementum, periodontal ligament and alveolar process. The periodontal disease affecting the soft tissue sorrounding the tooth without any alveolar loss, periodontal ligament or cementum and it is called as gingivitis. If it is untreatment as soon as possible then it will grow fast and infected the alveolar process resulting periodontitis. Gingival Recession is defined as the apical displacement of the gingival margin. Gingival recession showing first step in cemental damage, the exposure of the dentinal tubuli, causing pain and discomfort. Periodontal surgery is the continuing treatment in gingiva. Subpithelial connective tissue graft have been highly predictable in gingival resession therapy with respect to a high percentage of wound healing of the connective tissue.